PENDEKATAN DISCOVERY UNTUK MENINGKATKAN AKTIVITAS BELAJAR DAN PENGUASAAN KOSAKATA PADA SISWA KELAS B2 TK MUTIARA INSANI BANDAR LAMPUNG - Titi Aryani (LPPM STKIP PGRI Bandar Lampung, 2020)
The purpose of this study was to describe the improvement of vocabulary learning achievement by applying the discovery approach of B2 grade students of Mutiara Insani Kindergarten, Bandar Lampung. The method used in this research is Classroom Action Research (PTK). The research subjects were students of class B2 even Semester TK Mutiara Insani Bandar Lampung, totaling 20 students. Data obtained from observer observation sheet notes on the learning process planned by the researcher, learning activity sheet, and test sheet to determine learning achievement. The data were analyzed using simple statistics, namely the percentage. The action was carried out from January to March 2019. The results of the study were 65% active cycle 1 learning activity, 75% active cycle II increased 10%, 85% active cycle III, increased 10%. While learning achievement in cycle I completed 65%, cycle II completed 75%, increased by 10%, cycle III completed 95%, increased by 20%, and records of observers who partnered with researchers showed good average criteria. The conclusion of this research is that the application of discovery learning approach can increase vocabulary learning activity and achievement in class B2 students of Mutiara Insani Kindergarten, Bandar Lampung.